(3QSGFd ENhGf GdUaGs - (3eLehYI eDdajf (B( (3ENhGf GdUaG(B)s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai cJHfG QSGFd GNhGf GdUaG hNdGf GdhaG ai JgPjH GdfaS hUdGM GdGNdGb hGdGUObGA GdcQGe heGgjI GYQGVge ajgG s
(3BNQgG (B:s
(3hGYde jG CNj HCf GdMjhGfGJ GdcHjQI GdTeS ai Gdadc s
(3HgG fXGe GdJYbjHIs
(3JTJed Ydi QShe hCTcGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B902s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs